ANTARA RASA DAN ESTETIKA KOMODIFIKASI NILAI KONSUMSI PADA PANGAN SEBAGAI WUJUD EKSISTENSI - Raditya, Michael HB (Jurnal Kawistara, 2014)
Nowadays, massively development of food consumption makes many changes, including the humanbiological element, the eating activity. In Earlier, taste of food is a priority in exchange value, but everythingsbe changed because the new concept about presentation and appearance of food itself. The presentationof food becomes important and creates more value for the food. Appearance is the main stimulant for thefood to deciding the taste from the food itself. In deep researched, implicity, the condition emphasis thathappened about commodifiation of exchange value in food perspective. Discussing about value in food, isa form of commodification and has correlation with society existence. To solve the problem, ethnofraphyand art perspective method is a source to analyzing data, with interviews and literature studies as a sourceof data, to interpret and respond the phenomena. The results of researched had founded, art is the newelement in value exchange of food. Food and art created an aesthetic and enchant point, and giving ahigher price. The high consumerism pattern makes aesthetic food as a symbol of class existence. The highvalue on aesthetic food becomes a reference for society to show who they are. The food created, not onlybecause the food itself, but also the contextual makes the food more essential.